RELATIONSHIP BETWEEN THE WAKATOBI NATIONAL PARK ZONATION SYSTEM AND DYNAMICS OF CORAL REEF ECOSYSTEM CONDITION - Fikri Firmansyah; Adib Mustofa; Estradivar; Adrian Damora; Christian Novia N Handayani; Jill Harris; Gabby Ahmadia; Amkietiela; Klaas J. Teule; Sugiyanta; Veda Santiadji; Anton Wijonarno; Muhammad Yusuf (Pusat Kajian Sumberdaya Pesisir dan Lautan IPB, 2017)
The zonation can be evaluated by observing changes in ecosystem and social status in Wakatobi National Park (Taman Nasional Wakatobi – TNW). Coral reef ecosystem is one of the parameters indicating the effectiveness of zonation system. This study grouped TNW zones into No Take Zone (NTZ – area larang ambil; ZI, ZPB, ZPr) and use zone (UZ – area pemanfaatan; ZPL, ZPU) to determine impact of zonation implementation between 2009 – 2016 on coral reef ecosystem. Three parameters (benthic coverage, fish abundance and fish biomass) were determined by Point Intercept Transect (PIT) and underwater visual census (UVC) methods and all of these data were tested using two-way ANOVA. Hard coral coverage fluctuated between 19 – 32% however, NTZ and UZ had no significant hard coral cover differences (F=2,182, df=1, P=0,14). Abundance of carnivour fish (F=0,53, df=1, P=0,46) and herbivour fish (F=1,98, df=1, P=0,17) were similar between those two zones. Fish bombing and poisoning were two major threats until 2007. However, sand mining and waste management has overcome two previous major threats by 2017. Zonation system and its implementation can be one of mangement effectiveness indicators. Support Wakatobi National Park Authority, it is recommended to apply harvest control rules (HCR), regular patrol and monitoring and stakeholders capacity buiding. Keywords Benthic cover; fish abundance; fish biomass